From shock therapy to gradualism: Anti-inflationary policy in Germany from 1973 to 1979 - Armin Gutowski; Hans-Hagen Härtel; Hans-Eckart Scharrer (Intereconomics, 1981)
A whole range of economic solutions have been proposed in recent years in an endeavour to combat rising inflation. Of these, the discussion on a policy of gradualism vis-à-vis shock therapy has given rise to considerable controversy. In the light of this controversy the following article analyzes the German experience with anti-inflationary policy between 1973 and 1979 and draws some important conclusions.
Keywords: 330